2023
DOI: 10.1002/bmc.5569
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and serum pharmacochemistry revealed the preventive mechanism of Gushudan in kidney‐yang‐deficiency‐syndrome rats

Abstract: Kidney-yang-deficiency-syndrome (KYDS) is a metabolic disease caused by neuroendocrine disorder. Gushudan (GSD) is a traditional Chinese medicine prescription with the effect of nourishing kidney and strengthening bones. In this study, the mechanism of preventive effect of GSD on KYDS was explored by integrating metabolomics and serum pharmacochemistry. Reversed-phase/hydrophilic interaction chromatography-ultra-high-performance liquid chromatography-Quadrupole-Orbitrap high-resolution mass spectrometry (RP/HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Modern medical research has shown that KYDS is a metabolic disease associated with genetics and environment. Neuroendocrine disorders caused by dysfunction of the hypothalamic‐pituitary‐gonadal (HPG) axis are the main pathological mechanisms of KYDS (Lu et al, 2023; Pan et al, 2006). The main function of the HPG axis is to promote reproductive maturation by stimulating the gonads to produce sex hormones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern medical research has shown that KYDS is a metabolic disease associated with genetics and environment. Neuroendocrine disorders caused by dysfunction of the hypothalamic‐pituitary‐gonadal (HPG) axis are the main pathological mechanisms of KYDS (Lu et al, 2023; Pan et al, 2006). The main function of the HPG axis is to promote reproductive maturation by stimulating the gonads to produce sex hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed its prevention of KYDS. Metabolomics and serum medicinal chemistry methods have shown that 10 components of GSD, including Epimedium glycoside and Serpentine, in association with targets such as AKT1 and MAPK4, modulate signaling pathways such as PI3K‐AKT1, which is the key to the prevention of KYDS by GSD (Lu et al, 2022). Fecal metabolomics studies have revealed the role of intestinal flora imbalance in the pathogenesis of KYDS and the mechanism of GSD in preventing KYDS through the “gut‐kidney” axis (Tong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the integration of detection instruments is conducive to increasing the detection range of metabolites. MS and nuclear magnetic resonance (NMR) techniques are the main analytical methods in metabolomics research (Lu et al, 2022). Among them, ultra‐high‐performance liquid chromatography‐quadrupole time‐of‐flight‐mass spectrometry (UPLC‐QTOF‐MS) has high sensitivity and high resolution.…”
Section: Introductionmentioning
confidence: 99%